THE IMPACT OF K-POP ON YOUTUBE ONLINE MEDIA ON PATTERNS OF COMMUNICATION BETWEEN INDIVIDUALS IN INDOMYSOLAR BTS ARMY COMMUNITY IN SOLO - Widi Utama, Arga; Wangi, Maya Sekar; Siswanta, Siswanta (Solidaritas, 2024)
Bangtan Boy ( BTS ) is a South Korean boyband that has attraced a lot of young peoples attention, so that it is not uncommon for communities to form based on the same hobbies. One of the communities formed is INDOMYSOLAR which is based in Solo City. The way fans enjoy BTS's work is by listening to their music via the online media YouTube. This hobby ultimately had an impact, especially in communication patterns between individual community members. This research aims to determine the impact of K-Pop on the online media YouTube on communication patterns between individuals in the INDOMYSOLAR community. In this research, researchers used descriptive qualitative methods which intended to describe communication patterns between individuals in the INDOMYSOLAR community. In order to obtain data for this research, researchers used observation, documentation and interviews with purposive sampling techniques. In order to provide relevant research results, researchers use source triangulation, technique triangulation, and time triangulation which can be used as data validity. The data that has been obtained is then analyzed using the Miles and Huberman analysis method. The results of this research explain the impact of changes in communication patterns of INDOMYSOLAR community members. Where before getting to know K-Pop, the members communicated using Indonesian and Javanese. Then after getting to know K-Pop, there was the addition of a new language, namely Korean, in the members' communication patterns. With code mixing and outer mixing language patterns, making the use of Korean a characteristic in the communication process between members of the INDOMYSOLAR community. Keywords: BTS, Change in Communication Pattern, K-Pop